USING TIMELINE AND CONCEPT QUESTIONS AS MEDIA TO DIFFERENTIATE SIMPLE PAST, SIMPLE PRESENT, AND SIMPLE FUTURE TENSE IN UNIVERSITY LEVEL - Ihsan Pratama; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
This paper is aimed to discuss about the use of the Timeline and Concept Questions to differentiate between simple past, simple present, and simple future tense in university level. This media is expected to helps students to understand the differentiate between simple past, simple present, and simple future tense. The activity done by the students can be clasified into three steps. First, students are introduced to the timeline and cconcept questions and its relation to the tenses. Second, students are asked to fill the timeline based on the sentences that is learned whether its belong to simple past, simple present or simple future tense. Third, teacher gives some questions (concept questions)  to the students. This is to see how far students’ understanding about simple present tense and simple past tense. After applying this media, it is expected that the students can understand the abstract concept of simple past tense, simple present tense, and simple past tense.